Pengunaan Metode Problem Solving Dalam Meningkatkan Aspek Kognitif Siswa Kelas VIII Mata Pelajaran IPS - Java Putra Sanjaya; Binti Maunah (Pusat Riset dan Inovasi Nasional, 2023)
The background of this research is the students' cognitive decline in social studies at SMPN 1 Ngantru Tulungagung. The learning method applied still uses conventional methods, namely the lecture method. When learning takes place, not many students feel bored or bored with what the teacher says. The researcher formulated the research focus as follows: 1) What is the Preparation Stage for Using the Problem Solving Method in Improving the Cognitive Aspects of Grade VIII Students at SMPN 1 Ngantru Tulungagung, 2) What is the Process of Using the Problem Solving Method in Improving Cognitive Aspects of Students in Social Studies Learning in Class VIII at SMPN 1 Ngantru Tulungagung, 3) What are the Results of Using the Problem Solving Method in Improving Students' Cognitive Aspects in Social Studies Learning in Class VIII of SMPN 1 Ngantru Tulungagung. The purpose of this research is to describe the preparation, use, and results of using problem solving methods at SMPN 1 Ngantru Tulungagung to improve students' cognitive aspects. This research is a descriptive qualitative research, using data collection methods of in-depth interviews, participant observation, and documentation. Data analysis techniques use data reduction, data presentation, and conclusions or verification.